The Effect of Selective Plyometric Exercises Using an Unstable Surface on the Movement Performance of Basketball Players - Parisa Sedaghati (The Society of Aging and Physical Activity (SAPA), 2018)
Background. Body adaptations and the high level of achievement in different sporting fields depend on the degree of fitness and training. Hence, it is important for basketball players to have suitable body fitness for tactics and skill performance. Objectives. The present study aims to investigate the effect of selective plyometric exercises using an unstable surface on the movement performance of female basketball players. Methods. In this pre-/post-designed clinical trial, the subjects were selected from among qualified female basketball players (n=24) having a history of two-year regular specialized training in a team considered as elite. They were randomly assigned into two, experiment (age: 20.25±2.34, training history: 2.55±0.29, and BMI: 23.28±0.93) and control (age: 21.16±2.79, training history: 2.60±0.75, and BMI: 24.80±1.04) groups. The experiment group performed for eight weeks (three sessions each week with a duration of 80 min/session) progressive plyometric exercises on an unstable surface. The assessment of dependent variables was performed using functional movement screening and the star excursion balance test. The results of the control and experiment groups were compared using multivariate covariance and post hoc Bonferroni test, while the pre- and post-test results were compared using the dependent t-test at a significance level of (p<0.05). Results. Comparing the results between the groups through the functional movement screening test and dynamic balance showed a significant difference. An improvement was seen in the results of relevant tests for the experiment group (p<0.001). Conclusion. The use of progressive plyometric exercise on an unstable surface shows an improvement in the results of the functional movement screening test and movement performance. This, in turn, results in an improvement in exercise performance.